2012
DOI: 10.1071/rdv24n1ab193
|View full text |Cite
|
Sign up to set email alerts
|

193 Insulin-Like Growth Factor-1 Exerts a Thermoprotective Role on Mitochondrial Function of Bovine Oocytes Exposed to Heat Shock

Abstract: The series of events associated with oocyte maturation are susceptible to disruption by elevated temperature. These events are regulated by a variety of growth factors, such as insulin-like growth factor-1 (IGF-1). Exposure of bovine oocytes to heat shock compromises oocyte competence and triggers apoptosis. It has been shown that cellular stresses often alter mitochondrial function and activate the mitochondrial apoptotic cascade. Therefore, the objective of this study was to determine the effect of heat shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the current study, we found a higher proportion of TUNEL-positive oocytes in the HS versus C group, and IGF-I decreased the proportion of TUNEL-positive oocytes to the level of the C group. In support of these findings, Ispada et al (2010Ispada et al ( , 2011 reported that IGF-I reversed HS-induced apoptosis in bovine oocytes. In contrast, Zhandi et al (2009) reported that IGF-I increased the proportion of TUNEL-positive oocytes when matured at 41°C but not at 38.5°C.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In the current study, we found a higher proportion of TUNEL-positive oocytes in the HS versus C group, and IGF-I decreased the proportion of TUNEL-positive oocytes to the level of the C group. In support of these findings, Ispada et al (2010Ispada et al ( , 2011 reported that IGF-I reversed HS-induced apoptosis in bovine oocytes. In contrast, Zhandi et al (2009) reported that IGF-I increased the proportion of TUNEL-positive oocytes when matured at 41°C but not at 38.5°C.…”
Section: Discussionmentioning
confidence: 75%
“…In support of these findings, Ispada et al . (2010, 2011) reported that IGF-I reversed HS-induced apoptosis in bovine oocytes. In contrast, Zhandi et al .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the transport and distribution of cytoplasmic organelles such as mitochondria as well as chromosomes separation during fertilization and cleavage are compromised (Ju et al, 2005). Moreover, increased oocyte DNA fragmentation (TUNEL positive) (Ispada et al, 2011), a characteristic of apoptosis, accompanied with reduced nuclear maturation, cleavage and blastocyst rates after exposing to HS (Paula-Lopes et al, 2008), suggesting activation of the heat-induced mitochondrial apoptotic pathway in bovine oocytes. Impairment of nutrition is another possible way by which HS can affect the oocyte quality (Fig.…”
Section: Heat Stressmentioning
confidence: 96%
“…Exposure of bovine oocytes to heat shock reduces oocyte mitochondrial activity (Ispada et al, 2011;Gendelman and Roth, 2012a). HS produces excessive ROS, induces apoptosis, and/or reduces the mitochondrial membrane potential in bovine oocytes (Soto and Smith, 2009).…”
Section: Heat Stressmentioning
confidence: 99%